Sensitivity of Kupffer cells and liver sinusoidal endothelial cells to ricin toxin and ricin toxin–Ab complexes. Issue 5 (16th July 2019) - Mooney, Bridget; Torres-Velez, Fernando J; Doering, Jennifer; Ehrbar, Dylan J; Mantis, Nicholas J
Abstract: Ricin toxin is a plant-derived, ribosome-inactivating protein that is rapidly cleared from circulation by Kupffer cells (KCs) and liver sinusoidal endothelial cells (LSECs)—with fatal consequences. Rather than being inactivated, ricin evades normal degradative pathways and kills both KCs and LSECs with remarkable efficiency. Uptake of ricin by these 2 specialized cell types in the liver occurs by 2 parallel routes: a "lactose-sensitive" pathway mediated by ricin's galactose/N-acetylgalactosamine-specific lectin subunit (RTB), and a "mannose-sensitive" pathway mediated by the mannose receptor (MR; CD206) or other C-type lectins capable of recognizing the mannose-side chains displayed on ricin's A (RTA) and B subunits. In this report, we investigated the capacity of a collection of ricin-specific mouse MAb and camelid single-domain (VH H) antibodies to protect KCs and LSECs from ricin-induced killing. In the case of KCs, individual MAbs against RTA or RTB afforded near complete protection against ricin in ex vivo and in vivo challenge studies. In contrast, individual MAbs or VH Hs afforded little (<40%) or even no protection to LSECs against ricin-induced death. Complete protection of LSECs was only achieved with MAb or VH H cocktails, with the most effective mixtures targeting RTA and RTB simultaneously. Although the exact mechanisms of protection of LSECs remain unknown, evidence indicates that the Ab cocktails exert their effects on the mannose-sensitive uptake pathway without the need for Fcγ receptor involvement. In addition to advancing our understanding of how toxins and small immune complexes are processed by KCs and LSECs, our study has important implications for the development of Ab-based therapies designed to prevent or treat ricin exposure should the toxin be weaponized. Graphical Abstract: Protection of Kupffer cells (KCs) and liver sinusoidal endothelial cells (LSECs) from the toxic effects of ricin is achievable with combinations of monoclonal antibodies.